Resilience partially mediates the relationship of academic self-concept with self-adjustment among students with disabilities: Resiliensi memediasi sebagian hubungan konsep diri akademik dengan penyesuaian diri pada mahasiswa dengan disabilitas - Ulifa; Zohrah; Perwira Dara, Yuliezar; Faizah (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
The present study examines the role of resilience as a mediator between the relationship of academic self-concept with self-adjustment among students with disabilities during the covid 19 pandemic. The results of this correlational study (N = 92 students with disabilities) showed that students with disabilities who possess a more positive academic self-concept tended to be more resilient than their peers with a lower positive academic self-concept. Highly resilient students, in turn, tended to be better self-adjusted than their lesser resilient counterparts. Mediation analysis suggested that resilience partially mediated the relationship between academic self-concept with self-adjustment. Keywords: academic self-concept, disabled students, adjustment, resilience Penelitian ini mengkaji tentang peran resiliensi sebagai mediator antara hubungan konsep diri akademik dengan penyesuaian diri pada mahasiswa difabel selama masa pandemi covid 19. Hasil penelitian korelasional ini (N = 92 siswa penyandang disabilitas) menunjukkan bahwa siswa penyandang disabilitas yang memiliki konsep diri akademik yang lebih positif cenderung lebih resilien dibandingkan mereka yang memiliki konsep diri akademik yang kurang positif. Siswa yang memiliki resiliensi tinggi, pada gilirannya, cenderung dapat menyesuaikan diri dengan lebih baik daripada mereka yang kurang resilien. Analisis mediasi menunjukkan bahwa resiliensi secara parsial memediasi hubungan antara konsep diri akademik dengan penyesuaian diri. Kata kunci: konsep diri akademik, mahasiswa disabilitas, penyesuaian diri, resiliensi